PREDICTION OF PREMATURE OVARIAN INSUFFICIENCY BASED ON SOME BIOCHEMICAL MARKERS - Bobokhonova Mukhayyokhon Mominjonovna, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: Premature ovarian insufficiency (POI), a major reproductive health concern for women under the age of forty, significantly influences fertility potential, hormonal balance, metabolic state, and quality of life. This condition is characterized by a reduction in both the quantity and quality of ovarian follicles long before natural menopause, resulting in diminished estrogen production, irregular menstrual cycles, and an early onset of menopausal symptoms. Contemporary advances in reproductive medicine and molecular biology have provided deep insights into the pathophysiological mechanisms underlying POI as well as the identification of critical biochemical markers that can assist in its early diagnosis and prediction. The reliability, reproducibility, and practicality of these biochemical markers are central to modern approaches in reproductive endocrinology, particularly as they allow clinicians to anticipate, counsel, and intervene in the disease process well before irreversible ovarian failure sets in.